PENGARUH PENGGUNAAN BONEKA TANGAN UNTUK MENINGKATKAN KEMAMPUAN BICARA ANAK USIA DINI - Muchamad Arif; Nopitasari Nopitasari (Universitas Narotama, 2021)
This research aimed to determine the use of hand puppets to improve children's speaking skills, especially in storytelling at Tk Melati Surabaya. This school is located on Jalan Jl. Mulyorejo Selatan II/19 Surabaya. The sample was Kindergarten A students; 25 children. It used a qualitative descriptive method. It focused on how to apply the use of hand puppets to improve children's speaking skills at Tk Melati Surabaya. There were 3 times observations in three meetings. Each meeting, they got a different fairy tale. The results showed that students felt happy, cheerful, enthusiastic and enthusiastic participating in the teaching-learning activities. Keywords: hand puppet, fairy tale, talk, children